THE GOVERNMENT TRANSFERS AND THE FLYPAPER EFFECT PHENOMENON OF CITY/DIGENCY AREA IN JAVA ISLAND - Puspita, Regina; Wiralaga, Harya Kuncara; Herlitah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
Intergovernmental transfers play an important role as a source of regional income to reduce thegap between demand and income. The purpose of this study was to determine the effect of GRDP,DAU, and Population Density in metropolitan and non-metropolitan areas in Java in 2019 andto determine the effect of taxes and DAU in provinces with high DAU and provinces with lowDAU in Java in 2010-2019. In addition, this study was also conducted to analyze the causes ofthe flypaper effect phenomenon in Java. Secondary data used are cross section data fromthe BPS of each province and panel data from the DJPK. The results of research using multiplelinear regression method with E-Views SV.11 software show that GRDP and DAU have apositive and significant effect on regional spending in metropolitan and non-metropolitanareas. DAU and taxes have a positive and significant effect on regional spending inprovinces with high and low DAU. Population Density only has a positive and significant effecton regional spending in metropolitan areas. The flypaper effect phenomenon occurs throughoutJava.